The seasonal and lifetime incidence of low back pain in South African male first league squash players - Burden, Stephen Barry (MRC/UCT RU for Exercise and Sport Medicine, 2017)
Previous studies have been conducted to determine the incidence of low back pain (LBP) in both the general population as well as in participants of different sporting activities. The purpose of this study was to determine the seasonal and lifetime incidence of LBP in male first league squash players.